Pengantar Tentang Konsep Dasar Siaran Radio TV dan Multimedia Bermuatan Dakwah - Efendi, Erwan; Syarif, Adam; Syahrini, Elvi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Da'wah through multimedia TV radio is one of the contemporary da'wah that can be enjoyed by everyone. Its use as a means of da'wah is a form of da'wah innovation. In the past, da'wah was synonymous with pulpits, mosques, prayer rooms, recitations and others. Even today, there are still many people who interpret da'wah only as a religious activity, even though da'wah is much more than that. Da'wah has the potential to motivate, remind, teach, all the good and bad things that must be known by humans. This type of research uses a qualitative approach. In this study the authors used qualitative methods with a library research approach. Library research is research that functions to obtain information from books, magazines, documents, historical records or in other words the facilities contained in library. The library approach is research with the activity of finding data from reading books and processing it, which in this case is a creative idea from an Islamic perspective. In the library research process, the library is the main place to get relevant data and information to read and collect, study and record. The results of this study found that innovation in da'wah is the use of television radio and multimedia in da'wah activities that have an important role as a tool or media in conveying da'wah. A da'wah must use multimedia in preaching as a strategy so that his da'wah can be easily accepted by mad'u and the purpose of da'wah is achieved.